Implementation of UCD with a kanban board to build an interaction design for an animal recognition application - Ariyana, Renna Yanwastika; Nurnawati, Erna Kumalasari; Ath-Thaariq, Muhammad Rizqy; Wahyudi, Putu Widi (SHM Publisher, 2023)
Studying types of animals is one way to expand knowledge about living creatures on earth. By introducing types of animals, especially children, it will help increase emotional intelligence, creativity and imagination of living creatures as a basis for understanding the diversity of creatures on earth. Every child certainly has different abilities and development, in general children will experience significant progress between the ages of 3 and 6 years, so at this age it is very appropriate to introduce types of animals packaged in interactive multimedia as a medium for learning. Providing knowledge about types of animals will expand knowledge about nature, build emotional intelligence and cognitive abilities which are important in their growth. In this research, an application for recognizing animals for children will be created that implements the User Centered Design (UCD) method with a kanban board, which is an alternative development approach that focuses on the needs and preferences of users at each stage of development, so that it is hoped that the application being developed will meet their desires and needs. user. The final result of this research is an animal recognition application, which implements the UCD method in UI/UX development and the Kanban framework in team work processes.